The effect of the behavioral counseling on developing self-affirmation among a sample of delinquents Enrolled in the Social Observation House in Medina - Al-Harbi, Abdulkarim Abdulaziz Marshoud (Journal of Educational and Psychological Sciences, 2021)
This study aimed to investigate the effect of behavioral counseling on the development of self- affirmation among a sample of delinquents, perpetrators of theft and moral crimes, who joined the social observation in Medina, and this included two groups, an experimental group and another control group, and conducting pre and post measurements of self- affirmation.The study sample consisted of (24) event from inmates of the social observation house in Medina who obtained low scores on the self- affirmation scale, they were divided into two groups: (an experimental group consisting of (12) events, and a control group consisting of (12) events, and the (Ratus) scale was applied to measure self-affirmation, in addition to a behavioral counseling program in developing self-affirmation prepared by the researcher, which consisted of (13) behavioral counseling session over two and a half months, and the duration of each session is (60) minutes.The results of the study resulted in statistically significant differences between the average scores of the members of the experimental and control groups after applying the program, and the differences came in favor of the experimental group.The researcher recommended that there should be an intensification and development of behavioral counseling programs that related to the development of self-affirmation among some delinquents, and with different guidance methods as well.
Keywords: behavioral counseling; self-affirmation; delinquents; social observation house